Fostering Meaning in Residency to Curb the Epidemic of Resident Burnout: Recommendations From Four Chief Medical Residents. (9th July 2019) - Berg, David D.; Divakaran, Sanjay; Stern, Robert M.; Warner, Lindsay N.
Abstract : Burnout has become commonplace in residency training, affecting more than half of residents and having negative implications for both their well-being and their ability to care for patients. During the authors' year as chief medical residents at Brigham and Women's Hospital in 2017-2018, they became intimately familiar with the burnout epidemic in residency training. The authors argue that addressing resident burnout requires residency programs and teaching hospitals to focus not on the individual contributors to burnout, but instead on fostering meaning within residency to help residents find purpose and professional satisfaction in their work. In this Perspective, they highlight four important elements of residency that provide meaning: patient care, intellectual engagement, respect, and community. Patient care, intellectual engagement, and community provide residents with a focus that is larger than themselves, while respect is necessary for a resident's sense of belonging. The authors provide examples from their own experiences and from the literature to suggest ways in which residency programs and teaching hospitals can strengthen each of these elements within residency and curb the epidemic of burnout.